Development of a new colorimetric system for masticatory performance evaluation / Yaman Mustafa Al-Yousof - Yaman Mustafa, Al-Yousof (2019)
The two-color mixing ability test has been recently introduced for objective assessment of masticatory performance. However, the ideal bicolor specimens have not yet been identified, and the color analysis of digital images requires improvement. The purpose of this clinical study was to formulate a custom-made, two-color chewing gum and to develop a new image-processing method for color mixing analysis. Specimens of red-green (RG) chewing gum were prepared as a bicolor test food. A total of 300 gums were masticated by 20 healthy volunteers (mean age 21 ±3.3 years) for 3, 6, 9, 15, and 25 mastication cycles. The boluses were retrieved, flattened to 1-mm-thick wafers, and scanned with a flatbed scanner. The digital images were analyzed using ImageJ software equipped with a custom-built plug-in Mastimeter©. Mastication Index (MI) was derived from the regression function using both spatial and value colorimetric parameters as predictors of the number of mastication cycles. Validity was assessed by the Pearson correlation between the Mastication Index and concurrent measurements using a previously well-established method, XYLITOL color-changeable gum, within a group of 10 dentate individuals and 10 denture wearers. Furthermore, the hardness and mass of RG chewing gum were measured before and after mastication. Hardness loss (%) and mass loss (%) were then calculated and compared with those of a commercially available chewing gum. Multiple regression analysis demonstrated a strong relationship between the color mixture and the number of mastication cycles (r2=0.81, P<.001). Independent samples t-test showed a significant difference in MI between dentate individuals and denture wearers (P<.001). Significant correlation was observed between the MI and XYLITOL outcomes (r=0.82, P<.001). The hardness loss and mass loss of RG chewing gum were significantly lower than those of the commercial chewing gum (P<.001). v In conclusion, Mastimeter© seems valid and has the potential for evaluating masticatory performance in both the research and clinical settings.